A cognitive behavioural intervention for low self‐esteem in young people who have experienced stigma, prejudice, or discrimination: An uncontrolled acceptability and feasibility study. (29th August 2021) - Langford, Katie; McMullen, Katrina; Bridge, Livia; Rai, Lovedeep; Smith, Patrick; Rimes, Katharine A.
Abstract : Objectives: Stigma has been found to be associated with lower self‐esteem, which increases the risk of difficulties across life domains including vulnerability to mental health problems. There are no previous studies of interventions for people experiencing low self‐esteem in the context of different stigmatized characteristics. This study evaluated feasibility, acceptability, and preliminary outcomes of an intervention targeting low self‐esteem in stigmatized people aged 16–24 years. Design: An uncontrolled study with repeated measures. Method: People with a range of stigmatized characteristics, who had low self‐esteem and associated impaired daily functioning, were recruited from the general population. The individual six‐session cognitive behavioural intervention had modules chosen according to participants' formulations. The CBT included compassion‐focussed therapy methods and was informed by stigma research. Feasibility was assessed in relation to recruitment, retention, and protocol adherence. Acceptability was assessed through participant feedback. Questionnaires assessing self‐esteem, functioning impairments, depression, anxiety, self‐criticism, self‐compassion, and responses to prejudice and discrimination were administered at baseline, pre‐, mid‐, post‐intervention, and two‐month follow‐up. Results: Forty‐four people completed screening; 73% were eligible. Of these, 78% consented and 69% ( N = 22) started the intervention. Eighteen (82%) participants completed, and four dropped out. Follow‐up measures were completed by all treatment completers. Treatment completers reported the intervention was useful, improved their self‐esteem and coping, and would recommend it. Ratings of usefulness and frequency of use of intervention components were high at post‐treatment and follow‐up. Conclusions: The intervention was feasible and highly acceptable to treatment completers. This suggests the intervention warrants investigation in a randomized‐controlled trial. Practitioner points: Young people with low self‐esteem whom have been negatively affected by stigma may wish to access support and be willing to engage in psychological interventions. Cognitive behavioural therapy may be helpful for young people with low self‐esteem who have experienced stigma, prejudice, or discrimination. Cognitive behavioural techniques such as self‐compassionate thought records and behavioural experiments were considered acceptable and helpful by young people whose self‐esteem has been affected by stigma. Addressing responses to stigma in therapy, such as rumination, avoidance, and perfectionism, appears to be feasible and acceptable.